Barriers and facilitators of school-based obesity prevention interventions: a qualitative study from the perspectives of primary school headteachers - Mohamed Saleh; Maryam Ba-Break; Asma Abahussin (Journal of Health, Population and Nutrition)
Abstract Background Childhood obesity is a growing global health issue. The World Health Organization identifies obesity as a significant risk factor for Non-Communicable Diseases and considers it a pandemic. This study aimed to investigate headteachers' perspectives and practices concerning childhood obesity prevention interventions in primary schools highlighting the barriers and facilitators for those interventions. Methods This qualitative study used a phenomenological approach and semi-structured interviews with headteachers of primary schools in the West Yorkshire area, UK. The collected data was transcribed and analysed using inductive thematic analysis. Results A total of 32 interviews with headteachers were conducted. The data indicated that interventions meant to prevent childhood obesity in schools are influenced by a range of barriers and facilitators that are organized under the following seven key themes: (1) staff perception of obesity prevention at school; (2) school policies on eating at schools; (3) School curriculum on healthy diets and physical activities; (4) role models at school; (5) partnership with parents; (6) extra-curricular activities on healthy diets and physical activities; (7) School capacity and resources. Conclusions Childhood obesity prevention interventions vary across UK schools depending on staff and head teachers' beliefs, awareness, commitments, school resources, parents' involvement and parents’ awareness, income, and culture. The study suggests raising awareness of childhood obesity among parents and staff, involving external partners like school nurses for training, making all primary pupils eligible for free meals, and providing schools with guidance on securing government funding. It provides a foundation for improving school-based strategies that indirectly contribute to better health outcomes for children.